Estilos de Aprendizaje de Estudiantes y Docentes de Primer y Segundo Año de la Carrera de Medicina Veterinaria en Concepción, Chile - Luzio Q., Alvaro (2015)
The current pedagogical approaches place in the student an active role in the learning process. The teacher is a facilitator who intervenes and helps in the learning process. In this sense, the learning styles emerge as a valuable pedagogical tool for both students and for teachers. They are closely related to the way students learn, to the teachers teaching style and how both interact in the teaching-learning relationship. From the point of view of a pedagogical approach, the model of Kolb’s learning styles classifies them as Active, Reflective, Theoretical, and Pragmatic. The present study identifies the learning styles of students and teachers in the first and second year of Veterinary Medicine at the University of Santo Tomas, in Concepción, Chile by applying the Honey and Alonso learning styles questionnaire (CHAEA). The questionnaire was applied to all students (n=39) and teachers (n=17) of the first two years of the career. The results indicated a moderate preference towards reflective learning style on students and teachers; however, no statistical difference was found between learning styles.